Ion Transporters From Basic Properties to Medical Treatment - Sevcikova Tomaskova, Zuzana (Biochemistry, 2022)
Ion transporters are membrane proteins that allow the passage of ions or charged small molecules through the lipid membrane. They are present in every cell of every organism. The group of ion transporters comprises different types of ion pumps, ion exchangers, and ion channels. This book focuses mostly on ion channels, which represent the biggest subset of ion transporters. Ion transporters, especially ion channels, are of imminent interest in the field of life sciences with possible therapeutic outcomes. Each piece of knowledge that can help us understand their role and function is worth noticing. This book provides a comprehensive overview of ion channels, including their diversity and functions in physiology and pathophysiology.